Экспресс-диагностика электрохимических аккумуляторов энергоустановок подвижных объектов - Азарнов, Александр Леонидович; Безручко, Константин Васильевич; Лазненко, Виктор Иванович; Синченко, Светлана Владимировна; Харченко, Андрей Анатолиевич (НТУ "ХПИ", 2017)
Рассмотрено сущность метода экспресс-диагностики электрохимических аккумуляторов. Приведены результаты экспериментального исследования никель-кадмиевого аккумулятора НК-125 при различных степенях заряженности. Представлены основные результаты экспериментальных исследований никель-кадмиевых аккумуляторов, вошедшие в математическую модель определения состояния электрохимических аккумуляторов в составе энергоустановок подвижных объектов. Построена математическая модель для диагностирования электрохимического аккумулятора. Проведено сравнение результатов расчетов с экспериментальными результатами.

Essentiality of method of express-diagnostics of electrochemical accumulators is considered. The results of experimental studies of nickel-cadmium batteries with different charge level shown. Rapid diagnosis base on the impact on the battery variables in the sign of the current pulses, allows you to define the parameters and characteristics of the battery in a short time, on a range of parameters and without interfering with the battery operation. The main experimental results of nickel-cadmium batteries are presented. These results were included in the mathematical model of determining the state of the electrochemical batteries as a part of power plants. A mathematical model for the diagnosis of an electro-chemical battery is built. The comparison of the calculation results with the experimental results conducted.
Rapid diagnosis of electrochemical batteries power plants moving objects
Keywords: диагностирование; математическая модель; вольт-амперная характеристика; разрядная характеристика; energy installation; mathematical model; current-voltage characteristic